2017
DOI: 10.1515/forj-2017-0006
|View full text |Cite
|
Sign up to set email alerts
|

Structure and dynamics of spruce-beech-fir forests in Nature Reserves of the Orlické hory Mts. in relation to ungulate game

Abstract: Knowledge of the structure and dynamics of near-natural mixed forests is a key factor for ecologically oriented management of forest ecosystems. The development of these model forests mostly takes place continually without any pronounced disturbances. Natural regeneration can be locally limited by ungulate browsing. The paper was focused on the structure and development of forest stands with emphasis on natural regeneration in relation to ungulates in Černý důl Nature Reserve and Trčkov National Nature Reserve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 71 publications
(71 reference statements)
1
18
0
Order By: Relevance
“…The attractiveness of fir, rowan and sycamore for game was also confirmed in other part of Czechia (Vacek et al 2014a(Vacek et al , b, 2018, Slovakia (Konôpka & Pajtík 2015), Germany (Ammer 1996) and Italy (Motta 2003). The recommendation for limiting the game damage and protection of valuable admixed tree species is reduction of still increasing ungulate population, building of overwinter preserve, feeding of game in selected localities, reliable fencing of stands, establishing of fields for game or reintroduction of predators (Vrška et al 2001;Cukor et al 2017;Vacek 2017;Cukor et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The attractiveness of fir, rowan and sycamore for game was also confirmed in other part of Czechia (Vacek et al 2014a(Vacek et al , b, 2018, Slovakia (Konôpka & Pajtík 2015), Germany (Ammer 1996) and Italy (Motta 2003). The recommendation for limiting the game damage and protection of valuable admixed tree species is reduction of still increasing ungulate population, building of overwinter preserve, feeding of game in selected localities, reliable fencing of stands, establishing of fields for game or reintroduction of predators (Vrška et al 2001;Cukor et al 2017;Vacek 2017;Cukor et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…(Vacek et al, 2014;Slanař et al, 2017). Great losses were caused also by brown hare there (Vacek, 2017). Schulze et al (2014) reported that sycamore regeneration is damaged by red and roe deer to a greater extent than European beech regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, these processes should lead to the arrangement tions Vacek 2017) and mechanical or repellents protection with focusing on support of fir, sycamore maple and other species largely suffering from browsing seems to be necessary (Olesen & Madsen 2008;Häsler & Senn 2012).…”
Section: Discussionmentioning
confidence: 99%